DIMENSI SOSIOLOGI DALAM AKTIVITAS RITUAL UMAT HINDU DI PURA AGUNG JAGATNATHA DENPASAR - I Gusti Ketut Widana Widana; Ni Wayan Sadri Sadri; I Gde Widya Suksma Suksma; I Putu Dia Antara Antara (UNHI PRESS, 2023)
Abstract In essence, every Hindu ritual activity is a social action that cannot be separated from a touch of psychology. This means that what Hindus do with their various ritual activities is an expression of devotion shown through socio-religious behavior. Sociologically, the continuation of ritual activities is a form of social obedience in carrying out the teachings of Yadnya which is bound by communal/collegial ties based on traditional life. This article aims to reveal that there is a sociological dimension in every ritual activity (yadnya) of Hindus. This study was carried out using a qualitative approach using observation, interview and document study techniques, then presented in an interpretative descriptive manner. Keywords: harmonization, sociology, psychology, ritual.